Estratégias de ensino e recursos pedagógicos para o ensino de alunos com tdah em aulas de educação física - Costa, Camila Rodrigues [UNESP]; Moreira, Jaqueline Costa Castilho; Seabra, Manoel Osmar (FapUNIFESP (SciELO), 2015)
ADHD is a common neurobehavioral, multifactorial disorder, that is common in the population of schoolage children, whose main feature is a persistent pattern of inattention and or hyperactivity/impulsivity, which often results in emotional, social and above all, functional impairments. In this perspective, the research aimed to plan, implement and analyze an intervention program consisting of psychomotor, play activities and game strategies. The study was based on the adaptation of learning resources and teaching strategies used in physical education classes aiming to stimulate memory, attention and concentration in children with ADHD. The study included four students diagnosed between the ages of six and ten years, of both genders, enrolled in a regular teaching school. The scale of motor development was initially applied for data collection, in order to identify the motor condition of the students. Having obtained the data and after a documentary analysis, three thematic types of activities were selected and applied: psychomotor, play activities and strategy games. The instruments used were: participant observation with field journal registration and filming. Content analysis was used for data analysis and six categories were obtained: 1. Teacher / student and student / student bond; 2. Cooperative Work.; 3. Mediation; 4. Routine; 5. Resource Selection and 6. Environment. These categories could underpin representative discussions of a proposal for an Inclusive Physical Education program for students with ADHD, consistent with the possibility of establishing routines that can integrate memory stimuli, attention and concentration of these subjects.
Teaching strategies and pedagogical resources for teaching students with adhd in physical education classes
Keywords: Adapted physical education; Inclusive education; Pedagogical games; Play; Special education